Perovskite solar cell based on Moire lattice structure and preparation method thereof
By adopting a thin film preparation method of Moore structured structure in the perovskite solar cell, the problem of low energy conversion efficiency of perovskite solar cells has been solved, and high -efficiency light absorption and short -circuit current density are improved, reducing costs and processes. Complexity.
Patent Information
- Application Number
- CN202411693916.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-28
AI Technical Summary
The energy conversion efficiency of perovskite solar cells is lower than the theoretical limit, mainly due to the reduction of short-circuit current caused by light absorption loss. The existing technology is solved by adding light reflection structures and optical interference layers, but these methods increase costs and processes. Complexity, not universal or weather-resistant.
Adopt the Morl Crystal structure to enhance light absorption. By pressing the printed diffraction grating, the perovskite film is more compact, improves the intensity of crystalline, and extend the light of the sun in the film through the principle of light interference, forming the super crystal grid structure. Essence
The perovskite solar cell with lower light absorption, high short circuit current density and energy conversion efficiency, reduced process complexity and cost, and improved the stability and life of the device.
Smart Images

Figure CN119384149A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of perovskite solar cells, and in particular relates to a perovskite solar cell that adopts a moiré lattice structure to enhance light absorption and a preparation process method of a perovskite solar cell based on the structure. Background Art
[0002] Perovskite solar cells have been widely studied and applied in academia and industry due to their excellent photoelectric conversion performance and low production cost compared to silicon solar cells. The energy conversion efficiency of perovskite solar cells is still lower than its theoretical limit, and there is room for further improvement. One of the main reasons for the loss of actual energy conversion efficiency is the light absorption loss in perovskite solar cells, which leads to a reduction in short-circuit current. The loss of solar cells under illumination mainly comes from the inability to absorb photons with energy less than the band gap, parasitic absorption of conductive substrates and transport layer films, and surface reflection of perovskite films. Reducing light reflection in perovskite solar cells is currently a relatively easy way to increase photocurrent. This problem can be solved through effective photon management, and it is expected to achieve high-efficiency perovskite solar cells at low cost.
[0003] In order to increase light absorption and reduce light reflection in perovskite solar cells, in patent publication number CN117545286A, a high-reflection light-trapping structure is applied to the upper surface of the encapsulation film of the perovskite solar cell. The high-reflection light-trapping structure formed integrally on the encapsulation film increases the optical path and the number of reflections, thereby increasing the generation of photocarriers. In another patent publication number CN116981271A, the micro-light-concentrating layer and the anti-reflection and anti-transmittance layer are sequentially arranged on the light-incident surface of the perovskite component to increase the photocurrent of the component device by increasing the light scattering intensity and the thin film interference principle. However, this method of increasing the light absorption of solar cells by adding an additional anti-reflection light-trapping layer first increases the cost and process complexity, and requires a cost-effective balance. Secondly, limited by the principle of optical interference, the anti-reflection film only has the best reflection reduction effect on light with a wavelength of one-quarter the thickness of the film. For perovskite solar cells with different band gaps, the device light response peak wavelength is different, and the application of the anti-reflection film of the same structure is not universal. Moreover, anti-reflection and light-trapping structures generally use high-molecular polymer materials such as polymethyl methacrylate (PMMA) and polydimethylsiloxane (PDMS), which are prone to aging and degradation after long-term outdoor use. The weather resistance and long-term stability of the reflective layer need to be tested and verified. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a perovskite solar cell based on a moiré lattice structure and a perovskite solar cell using a perovskite film prepared by the method as a photoactive layer, and to produce a perovskite solar cell with low light absorption loss, high short-circuit current density and energy conversion efficiency through a simple process and low-cost film preparation method. The method of the present invention has three advantages over other methods for reducing light absorption loss: 1) The method of preparing a diffraction grating by imprinting makes the perovskite film more compact and has a higher crystal strength; 2) The moiré lattice structure improves the light collection efficiency and enhances the short-circuit current and energy conversion efficiency of the perovskite solar cell; 3) The moiré lattice structure is based on the principle of light interference, which prolongs the optical path of sunlight in the perovskite film, so that a thinner semiconductor film is allowed to be used in the solar cell device, so that the lead content in the perovskite solar cell is reduced, which saves more raw materials and is more environmentally friendly.
[0005] The first aspect of the present invention provides a perovskite solar cell based on a moiré lattice structure, whose structure includes, from bottom to top, a substrate, a hole transport layer, a perovskite layer, a perovskite passivation layer, an electron transport layer, a hole blocking layer, and a back electrode; wherein the hole transport layer and the perovskite layer are sequentially deposited with a grating structure film rotated at a specific angle to form a moiré lattice structure.
[0006] Furthermore, the hole transport layer is a thin film with hole transport capability and a grating structure, and the grating spacing ranges from 0.01 to 1000 um. In some embodiments, the hole transport layer may be at least one of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), nickel oxide (NiOx), molybdenum trioxide (MoO3), cuprous iodide (CuI), and cuprous thiocyanate (CuSCN) with a grating pattern.
[0007] Furthermore, the perovskite layer has a grating structure, and the molecules are ABX 3 The structure has a grating spacing range of 0.01-1000 um; the A position is an organic cation, including CH 3 NH 3 + (MA + ), NH 2 CH=NH 2 + (FA + ), CH 3 CH 2 NH 3 + or Cs + At least one of the following, the B position is a metal cation, including Pb 2+Sn 2+ At least one of the following, X is a halogen anion, including F - , Cl - Br - ,I - At least one of .
[0008] Furthermore, the grating pattern direction of the hole transport layer forms a certain angle with the grating pattern direction of the perovskite layer, ranging from 0.01-89.99°.
[0009] Preferably, the hole transport layer grating and the perovskite layer grating form a moiré lattice structure with an angle of 10°.
[0010] Furthermore, the perovskite passivation layer is at least one of 4-fluorophenethylammonium chloride (4F-PEACl), phenethylammonium iodide (PEAI), butylammonium iodide (BAI), propylammonium iodide (PAI), 1,3-propylenediamine hydroiodide (PDADI), ethylenediamine hydroiodide (EDADI) or 1,8-octanediamine hydroiodide (ODADI).
[0011] Furthermore, the electron transport layer is a planar thin film with electron transport capability. In some embodiments, the electron transport layer may be zinc oxide (ZnO), tin dioxide (SnO 2 ), titanium dioxide (TiO 2 ), [6,6]-phenyl C 61 Methyl butyrate (PC 61 BM), carbon 60 (C 60 ) at least one of.
[0012] In one embodiment, the hole blocking layer is tin dioxide (SnO 2 ), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), (3-[6-(diphenylphosphino)-2-naphthyl]-1,10-phenanthroline) (Phen-NaDPO) and at least one of other phenanthroline derivatives.
[0013] The back electrode is at least one of gold (Au), silver (Ag), copper (Cu), and aluminum (Al).
[0014] Another aspect of the present invention provides a method for preparing a perovskite solar cell based on a moiré lattice structure. The moiré lattice structure of the present invention is obtained by rotating the thin films of the above two structures at a specific angle and depositing them in sequence. The method for preparing the hole transport layer and the perovskite film of the grating structure specifically comprises the following steps:
[0015] A substrate is provided, on which a hole transport layer, a perovskite layer, a perovskite passivation layer, an electron transport layer, a hole blocking layer and a back electrode are sequentially prepared, wherein the hole transport layer and the perovskite layer are prepared by laminating a PDMS film with a grating pattern, and the PDMS film with a grating pattern is deflected by 0.01-89.99° in the laminating direction of the hole transport layer and the perovskite layer.
[0016] In an optional embodiment, the preparation of the hole transport layer includes: spin coating the hole transport layer solution on the substrate, pressing a PDMS film having a grating pattern on the hole transport layer film and annealing, and peeling off the PDMS film to obtain a hole transport layer having a grating structure.
[0017] Furthermore, the hole transport layer solution includes a solute and a solvent, the solute can be selected from at least one of poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), poly-3 hexylthiophene (P3HT), nickel oxide (NiOx), molybdenum trioxide (MoO3), cuprous iodide (CuI), and cuprous thiocyanate (CuSCN), and the solvent can be selected from deionized water; the rotation speed of the hole transport layer solution spin coating can be 1000~6000 rpm.
[0018] Specifically, the annealing of the hole transport layer can be performed in two steps, the first step annealing temperature is 50° C., the time is 5 minutes, and the second step annealing temperature is 100° C., the time is 30 minutes.
[0019] In an optional embodiment, the preparation of the perovskite layer includes: spin coating a perovskite precursor solution on the hole transport layer to form a perovskite wet film, pressing the PDMS film having a grating pattern on the wet film, and peeling off the PDMS film after annealing to obtain a perovskite layer having a grating structure.
[0020] Furthermore, the perovskite precursor solution is CsI:FAI:PbI 2 :PbBr 2 Dissolved in DMF:DMSO with a molar ratio of x:(1-x):(y-1) / 2:(3-y) / 2, wherein 0<x<1, 0<y<3, and the solvent ratio is between 0-3:10-7, heated at 60°C with stirring for 12 h, and then filtered; the spin coating speed is 1000-6000 rpm.
[0021] Specifically, the annealing of the perovskite layer can be performed in two steps, the first step annealing temperature is 50° C., the time is 5 minutes, and the second step annealing temperature is 100° C., the time is 30 minutes.
[0022] Preferably, the PDMS film with the grating pattern is deflected by 10° in the pressing direction of the hole transport layer and the perovskite layer.
[0023] The preparation of the PDMS film is as follows: providing a digital versatile disc, ultrasonically cleaning in ethanol to remove the thin film on the surface of the disc, then drying it in an oven at 75° C. for 1 hour and then taking it out, casting polydimethylsiloxane (PDMS) on the digital surface of the disc, then curing it in a vacuum oven for 4 hours, and peeling the PDMS film with a grating pattern from the disc.
[0024] In an optional embodiment, the substrate is ultrasonically cleaned with acetone, deionized water and isopropyl alcohol before preparation, and cleaned in a plasma cleaner for 15 minutes.
[0025] Furthermore, the ultrasonic power is between 0 and 120 W, and the ultrasonic cleaning time is 30 min.
[0026] Furthermore, the perovskite passivation layer is prepared by spin coating a solution of at least one of the following materials: 4-fluorophenethylammonium chloride (4F-PEACl), phenethylammonium iodide (PEAI), butylammonium iodide (BAI), propylammonium iodide (PAI), 1,3-propylenediamine hydroiodide (PDADI), ethylenediamine hydroiodide (EDADI) or 1,8-octanediamine hydroiodide (ODADI).
[0027] Furthermore, the electron transport layer is obtained by evaporating at least one of the following materials: zinc oxide (ZnO), tin dioxide (SnO 2 ), titanium dioxide (TiO 2 ), [6,6]-phenyl C 61 Methyl butyrate (PC 61 BM), carbon 60 (C60); the hole blocking layer is obtained by evaporation of at least one of the following materials: tin dioxide (SnO 2 ), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), (3-[6-(diphenylphosphino)-2-naphthyl]-1,10-phenanthroline) (Phen-NaDPO) and other phenanthroline derivatives; the evaporation rate range is 0~2 Å / s, and the thickness range is 0~20 nm.
[0028] Furthermore, the back electrode is prepared by vacuum thermal evaporation of at least one of the following materials: gold (Au), silver (Ag), copper (Cu), and aluminum (Al).
[0029] The moiré lattice structure prepared by the above method is a superlattice structure produced when the grating structure film formed by the imprinted perovskite layer forms a specific angle with other two-dimensional nanomaterials (such as nickel oxide, tin oxide or the like) stacked layers. This structure can bring some unique advantages: 1) Quantum well effect: The quantum well formed in the moiré lattice limits carriers, enhances quantum confinement and energy state separation, improves charge collection efficiency, reduces recombination, and helps to improve the energy conversion efficiency of perovskite solar cells; 2) Exciton interaction: The exciton effect in the moiré structure can enhance light absorption, enhance the interaction between photons and perovskite films, increase nonlinear absorption, and improve optoelectronic performance; 3) Interface optimization: The interface between the moiré lattice layers has less defect state density, which can optimize carrier transport and reduce non-radiative recombination, improve charge extraction efficiency, and improve the stability and life of the battery.
[0030] The perovskite solar cell based on the moiré lattice structure prepared by the above method has three advantages over other similar solar cells: 1) The band gap of the perovskite material is tunable, which can adapt to the moiré lattice structure with different rotation angles, expanding the adaptability of process production; 2) The perovskite ion crystal type material can be prepared by simple low-temperature imprinting to prepare the grating structure film, which reduces the difficulty and cost of the preparation process of the moiré lattice structure; 3) The high absorption coefficient of the perovskite material allows the use of thinner moiré lattice structure films, which reduces the lead content in the perovskite solar cell, saves more raw materials, and is more environmentally friendly. These advantages of the perovskite solar cell with a moiré lattice structure demonstrate the potential in optoelectronic structure design, energy gap engineering, quantum physics and new phenomena, bringing performance improvements and new possibilities to the field of solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of a moiré lattice structure of a perovskite solar cell according to an embodiment of the present invention;
[0032] Figure 2 This is a schematic diagram of the structure of a perovskite solar cell according to an embodiment of the present invention;
[0033] Figure 3 IV curves of the perovskite solar cells in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention under AM 1.5G standard sunlight;
[0034] Figure 4 The external quantum efficiency spectra of the perovskite solar cells in Example 1, Comparative Example 1 and Comparative Example 2;
[0035] Figure 5 The UV-visible light absorption spectra of the perovskite films in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0036] 10. substrate; 20. hole transport layer; 30. perovskite layer; 40. perovskite passivation layer; 50. electron transport layer; 60. hole blocking layer; 70. back electrode. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0038] In the description of the present invention, unless otherwise specified, "multiple" means two or more; the terms "center", "longitudinal", "lateral", "up", "down", "left", "right", "inside", "outside", "front end", "rear end", "head", "tail", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate the orientation or position relationship based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third" and the like are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0039] The present invention mainly provides a perovskite solar cell based on a moiré lattice structure and a preparation method thereof. Figure 2 The perovskite cell includes a structure from bottom to top: a substrate 10, a hole transport layer 20, a perovskite layer 30, a perovskite passivation layer 40, an electron transport layer 50, a hole blocking layer 60 and a back electrode 70, wherein the hole transport layer 20 and the perovskite layer 30 are grating structures, and the grating directions have a certain angle to form a moiré lattice structure. Based on the principle of light interference, the optical path of sunlight in the perovskite film is extended, and the short-circuit current and energy conversion efficiency of the cell are improved. Combined with the solar cell structure, the preparation method of the solar cell described in the present application includes the steps of:
[0040] Step 1: Provide a substrate 10, and spin-coat a hole transport layer solution on the substrate 10 to form a hole transport layer film. Optionally, the substrate 10 is one of indium tin oxide conductive glass or fluorine-doped tin dioxide conductive glass.
[0041] Specifically, the substrate 10 is ultrasonically cleaned with acetone, deionized water and isopropanol for 15 min each before use, with an ultrasonic power of 0-120w and N 2 Blow dry and treat under oxygen plasma at 150 W for 120 s.
[0042] Optionally, the hole transport layer solution includes a solute and a solvent, the solute can be selected from at least one of poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA), poly-3 hexylthiophene (P3HT), nickel oxide (NiOx), molybdenum trioxide (MoO3), cuprous iodide (CuI), and cuprous thiocyanate (CuSCN), and the solvent can be selected from deionized water; in this embodiment, the hole transport layer solution 100ul concentration of 20 mg / ml NiO x Solution (the solvent is deionized water); the spin coating speed can be 1000~6000 rpm, preferably 4000 rpm for 30 s.
[0043] Step 2: Provide a PDMS film with a grating pattern, press it onto the hole transport layer film and anneal it, peel off the PDMS film, and obtain a hole transport layer 20 with a grating structure. Specifically, the annealing can be performed in two steps, the first step annealing temperature is 50°C, the time is 5 minutes, and the second step annealing temperature is 100°C, the time is 30 minutes.
[0044] Optionally, the PDMS film is prepared by providing a digital versatile disc, ultrasonically cleaning in ethanol to remove the thin film on the surface of the disc, then drying in an oven at 75°C for 1 hour and then taking it out, casting polydimethylsiloxane (PDMS) on the digital side of the disc, then curing it in a vacuum oven for 4 hours, and peeling the PDMS film with a grating pattern from the disc. The pitch of the grating pattern of the PDMS film is 0.01-1000 um, preferably 1 mm.
[0045] Step 3: Spin-coat the perovskite precursor solution on the hole transport layer 20 to form a perovskite wet film, press the PDMS film with the grating pattern on the wet film, and deflect the pressing position from the position in step 2 by 0.01-89.99°, preferably by 10°, and peel off the PDMS film after annealing to obtain a perovskite layer 30 with a grating structure. The annealing can also be performed in two steps, the first step annealing temperature is 50°C, the time is 5 minutes, and the second step annealing temperature is 100°C, and the time is 30 minutes.
[0046] See also Figure 1 The grating directions of the perovskite layer 30 and the hole transport layer 20 are deflected at an angle of 10°, forming a moiré lattice structure together. This structure will increase the optical path of sunlight in the film, thereby improving the short-circuit current and photoelectric conversion efficiency of the device.
[0047] In a specific embodiment, the perovskite precursor solution is CsI:FAI:PbI 2 :PbBr 2Dissolved in DMF:DMSO with a molar ratio of x:(1-x):(y-1) / 2:(3-y) / 2, wherein 0<x<1, 0<y<3, and the solvent ratio is between 0-3:10-7, heated at 60 ℃ and stirred for 12 h, then filtered, and the spin coating speed is 1000-6000 rpm.
[0048] Step 4: Spin-coat a perovskite passivation layer solution on the perovskite layer 30, and perform annealing to obtain a perovskite passivation layer 40. Optionally, the perovskite passivation layer solution is a solution of at least one material selected from the following: 4-fluorophenethylammonium chloride (4F-PEACl), phenethylammonium iodide (PEAI), butylammonium iodide (BAI), propylammonium iodide (PAI), 1,3-propylenediamine hydroiodide (PDADI), ethylenediamine hydroiodide (EDADI) or 1,8-octanediamine hydroiodide (ODADI).
[0049] Specifically, the perovskite passivation layer solution is selected from a PDADI solution with a concentration of 2.5 mg / ml (the solvent is isopropanol), and 150 ul of the perovskite passivation layer solution is coated on the surface of the perovskite layer 30, spin-coated at a rotation speed of 5000 rpm for 30 s, and then annealed at 100° C. for 5 min.
[0050] Step 5: Place the film obtained in the above step on a mask, and evaporate the electron transport layer material on the surface of the perovskite passivation layer 40 to form an electron transport layer 50. Optionally, the electron transport layer material is zinc oxide (ZnO), tin dioxide (SnO 2 ), titanium dioxide (TiO 2 ), [6,6]-phenyl C 61 Methyl butyrate (PC 61 BM), carbon 60 (C60); the evaporation rate range is 0~2 Å / s, and the thickness range is 0~20 nm.
[0051] Specifically, the evaporation vacuum degree is 1×10 -4 Pa, and 20 nm C60 material is evaporated at an evaporation rate of 0.1-0.15 Å / s to form an electron transport layer 50.
[0052] Step 6: Evaporate a hole blocking layer material on the electron transport layer 50 to form a hole blocking layer 60. Optionally, the hole blocking layer material is tin dioxide (SnO 2 ), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), (3-[6-(diphenylphosphino)-2-naphthyl]-1,10-phenanthroline) (Phen-NaDPO) and at least one of other phenanthroline derivatives.
[0053] Specifically, 5 nm BCP material is evaporated at an evaporation rate of 0.1-0.15 Å / s to obtain the hole blocking layer 60 .
[0054] Step 7: Evaporating electrode material on the hole blocking layer 60 to form a back electrode 70. Optionally, the back electrode 70 may be composed of a metal electrode such as Ag or Cu.
[0055] Specifically, the evaporation vacuum degree is 1×10 -4 Pa, the evaporation rate is 1 Å / s, and 100 nm Cu is evaporated to obtain the back electrode.
[0056] The perovskite solar cell based on the lattice structure and the preparation method provided in the embodiment of the present application utilizes the grating structure of the hole transport layer and the perovskite layer with a rotation angle to make the gratings on the upper and lower surfaces of the perovskite crystal form an angle to form a moiré lattice structure. The period of the generated moiré grating is:
[0057]
[0058] Where W is the period of the moiré pattern, d is the spacing of the grating, and θ is the rotation angle. The moiré lattice structure can reduce reflection and enhance the absorption of perovskite crystals in the visible light band. This effect mainly comes from the following three aspects: 1) The upper surface of the perovskite film with a grating structure has a nano-light trapping structure, which can increase the number of light reflections on the film surface and reduce direct reflection of the perovskite layer; 2) Using the nano double grating structure, the incident light can be effectively scattered and diffracted, greatly extending the light path in the perovskite layer and promoting the absorption of the perovskite; 3) The light intensity distribution in the perovskite film is adjusted by the moiré lattice structure as follows:
[0059]
[0060] The field enhancement in the perovskite layer enhances light absorption, where (x, y) is the spatial position, I is the light intensity, and A is 0 B 0 and A +1 B -1 They represent the coefficients of the zeroth harmonic and the positive and negative first harmonics in the Fourier series expansion, d is the grating spacing, and θ is the rotation angle.
[0061] The moiré lattice structure prepared by the above method is a superlattice structure produced when the grating structure film formed by the imprinted perovskite layer forms a specific angle with other two-dimensional nanomaterials (such as nickel oxide, tin oxide or the like) stacked layers. This structure can bring some unique advantages: 1) Quantum well effect: The quantum well formed in the moiré lattice limits carriers, enhances quantum confinement and energy state separation, improves charge collection efficiency, reduces recombination, and helps to improve the energy conversion efficiency of perovskite solar cells; 2) Exciton interaction: The exciton effect in the moiré structure can enhance light absorption, enhance the interaction between photons and perovskite films, increase nonlinear absorption, and improve optoelectronic performance; 3) Interface optimization: The interface between the moiré lattice layers has less defect state density, which can optimize carrier transport and reduce non-radiative recombination, improve charge extraction efficiency, and improve the stability and life of the battery.
[0062] In order to verify the performance of the perovskite solar cell prepared by the preparation method provided in the examples of the present application, the examples of the present application provide three groups of experiments for comparative demonstration, namely, Example 1, Comparative Example 1, and Comparative Example 2.
[0063] Embodiment 1:
[0064] This embodiment is a perovskite solar cell based on a moiré lattice structure prepared by the method of the present invention, wherein the grating rotation angle is 10°, and the preparation method specifically includes the following steps:
[0065] S1. Soak the digital versatile disc in ethanol and clean it ultrasonically in ethanol until the thin film on the surface of the disc is removed and rinsed with ethanol, then store it in an oven at 75°C for 1 hour. After drying, cast PDMS on the digital side of the disc and then cure it in a vacuum oven for 4 hours. Then, peel off the PDMS film with the grating pattern from the disc.
[0066] S2. Provide a conductive glass and ultrasonically clean it with acetone, deionized water and isopropanol for 15 min each. 2 Blow dry and treat in oxygen plasma at 150 W for 120 s;
[0067] S3, add 100 ul of 20 mg / ml NiO x The solution (solvent is deionized water) is coated on the surface of the plasma-cleaned conductive glass and spin-coated at 4000 rpm for 30 s. The PDMS film with the grating pattern described in step S1 is attached to the NiO xThe film was annealed in two steps. The first step was annealed at 50°C for 5 minutes and the second step was annealed at 100°C for 30 minutes. x The film is peeled off to obtain NiO with grating structure x film;
[0068] S4, CsI:FAI:PbI 2 :PbBr 2 Pb was dissolved in 1 ml of DMF:DMSO (4:1 v / v) mixed solvent at a molar ratio of 0.22:0.78:0.775:0.225. 2+ The ion concentration was 1.5 M. After heating and stirring at 60 °C for 12 h, Cs was filtered using a 0.45 μm filter head. 0.22 FA 0.78 Pb(I 0.85 Br 0.15 ) 3 Precursor solution. Apply 120 ul of perovskite precursor solution on NiO x The film surface was spin-coated at 4000 rpm for 30 s. After the spin coating was completed, the grating direction of the PDMS film with a grating pattern described in step S1 was aligned with the NiO film with a grating structure prepared in step S3. x The film's grating direction is aligned parallel, and after being rotated 10°, it is attached to the spin-coated perovskite wet film and subjected to two-step temperature co-annealing. The first step is annealing at 50°C for 5 minutes, and the second step is annealing at 100°C for 30 minutes. After annealing, the PDMS film is peeled off from the perovskite film to obtain a perovskite layer with a grating structure. x Grating film and Cs 0.22 FA 0.78 Pb(I 0.85 Br 0.15 ) 3 The perovskite grating film together forms a film with a moiré lattice structure;
[0069] S5. Prepare the perovskite passivation layer. Apply 150 ul of 2.5 mg / ml PDADI solution (solvent is isopropanol) on the surface of the perovskite layer, spin coat at 5000 rpm for 30 s, and then anneal at 100°C for 5 min.
[0070] S6, placing the film obtained in step S5 on the mask plate, placing it in the chamber of the evaporation machine, and -4Pa vacuum, evaporation was performed at a rate of 0.1-0.15Å / s to deposit a 20 nm C60 electron transport layer film. After evaporation was completed and completely cooled, a 5 nm BCP hole blocking layer film was evaporated at a rate of 0.1-0.15Å / s.
[0071] S7, finally at 1×10 -4 A 100 nm Cu electrode was evaporated at a rate of 1 Å / s under a vacuum degree of 1 Pa.
[0072] Comparative Example 1:
[0073] Comparative Example 1 provides a perovskite solar cell based on a grating structure, which has the same preparation steps as Example 1, except that in step S4, the perovskite layer film preparation method is to form a PDMS film with a grating pattern and a NiO x The grating direction of the film is aligned parallel to the perovskite film, and the grating structure film formed by co-annealing is NiO x The thin film and perovskite film only have a grating structure but do not form a moiré lattice structure.
[0074] Comparative Example 2:
[0075] Comparative Example 2 provides a perovskite solar cell with a conventional structure, except that NiO x The film and the perovskite film have the same structural features and preparation steps as Example 1 except that they are planar structures. Steps S3 and S4 in Comparative Example 2 are:
[0076] S3, add 100 ul of 20 mg / ml NiO x The solution (solvent is deionized water) was coated on the surface of the plasma-cleaned substrate, spin-coated at 4000 rpm for 30 s, and then the film was heated at 100 °C for 10 min.
[0077] S4, CsI:FAI:PbI 2 :PbBr 2 Pb was dissolved in 1 ml of DMF:DMSO (4:1 v / v) mixed solvent at a molar ratio of 0.22:0.78:0.775:0.225. 2+ The ion concentration was 1.5 M. After heating and stirring at 60 °C for 12 h, Cs was filtered using a 0.45 μm filter head. 0.22 FA 0.78 Pb(I 0.85 Br 0.15 ) 3Precursor solution. 120 ul of perovskite precursor solution was applied to the surface of the hole transport layer, spin-coated at 4000 rpm for 30 s, and then annealed at 100 °C for 10 min.
[0078] The JV curves of Example 1, Comparative Example 1 and Comparative Example 2 were measured under AM 1.5 G standard sunlight. Figure 3 As shown. The energy conversion efficiency of the perovskite solar cell based on the planar structure is 20.01%, while the energy conversion efficiency of the perovskite solar cell based on the grating structure is 20.68%. The improvement in energy conversion efficiency is mainly reflected in the increase in light absorption, thereby increasing the short-circuit current density. The energy conversion efficiency of the perovskite solar cell based on the moiré lattice structure prepared by the method of the present invention is 20.68%. Compared with the devices with planar structure and grating structure, the short-circuit current density has been greatly improved. From Figure 4 It can be seen that the increase in short-circuit current density is mainly due to the enhancement of the external quantum efficiency of light in the 400-700 nm band. Figure 5 As shown, the enhancement of the ultraviolet visible light absorption spectrum of Example 1 also proves the feasibility and effectiveness of the moiré lattice structure in the present invention in reducing light reflection loss and increasing sunlight absorption. The performance parameters of the solar cell are summarized in Table 1 below.
[0079] Table 1 Performance parameters of solar cells of Example 1, Comparative Example 1 and Comparative Example 2
[0080] sample Open circuit voltage (mV) <![CDATA[Short-circuit current density (mA / cm 2 )]]> Fill factor (%) Energy conversion efficiency (%) Example 1 1261.79 19.54 86.24 21.26 Comparative Example 1 1260.65 19.08 85.99 20.68 Comparative Example 2 1259.53 18.45 86.12 20.01
Claims
1. A perovskite solar cell based on a moiré lattice structure, characterized in that: Its structure includes, from bottom to top, a substrate, a hole transport layer, a perovskite layer, a perovskite passivation layer, an electron transport layer, a hole blocking layer, and a back electrode; wherein the hole transport layer and the perovskite layer are deposited in sequence with a grating structure film rotated at a specific angle to form a moiré lattice structure.
2. The perovskite solar cell based on a moiré lattice structure according to claim 1, characterized in that: The hole transport layer is a grating structure, and the grating spacing ranges from 0.01 to 1000 um.
3. The perovskite solar cell based on a moiré lattice structure according to claim 2, characterized in that: The hole transport layer is at least one of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly-3-hexylthiophene (P3HT), nickel oxide (NiOx), molybdenum trioxide (MoO3), cuprous iodide (CuI), and cuprous thiocyanate (CuSCN) with grating patterning.
4. The perovskite solar cell based on a moiré lattice structure according to claim 1, characterized in that: The perovskite layer has a grating structure, the molecule is ABX3 structure, and the grating spacing ranges from 0.01 to 1000 um; wherein the A position is an organic cation, including CH3NH3 + (MA + ), NH2CH=NH2 + (FA + )、CH3CH2NH3 + or Cs + At least one of the following, the B position is a metal cation, including Pb 2+ Sn 2+ At least one of the following, the X position is a halogen anion, including F - , Cl - Br - ,I - At least one of .
5. The perovskite solar cell based on a moiré lattice structure according to claim 1, characterized in that: The grating pattern direction of the hole transport layer forms a certain angle with the grating pattern direction of the perovskite layer, ranging from 0.01-89.99°.
6. The perovskite solar cell based on a moiré lattice structure according to claim 5, characterized in that: The hole transport layer grating and the perovskite layer grating form a moiré lattice structure with an angle of 10°.
7. The perovskite solar cell based on a moiré lattice structure according to claim 1, characterized in that: The perovskite passivation layer is at least one of 4-fluorophenethylammonium chloride (4F-PEACl), phenethylammonium iodide (PEAI), butylammonium iodide (BAI), propylammonium iodide (PAI), 1,3-propylenediamine hydroiodide (PDADI), ethylenediamine hydroiodide (EDADI) or 1,8-octanediamine hydroiodide (ODADI).
8. The perovskite solar cell based on a moiré lattice structure according to claim 1, characterized in that: The electron transport layer can be zinc oxide (ZnO), tin dioxide (SnO2), titanium dioxide (TiO2), [6,6]-phenyl C 61 Methyl butyrate (PC 61 BM), carbon 60 (C 60 ) at least one of.
9. The perovskite solar cell based on a moiré lattice structure according to claim 1, characterized in that: The hole blocking layer is at least one of tin dioxide (SnO2), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), (3-[6-(diphenylphosphino)-2-naphthyl]-1,10-phenanthroline) (Phen-NaDPO) and other phenanthroline derivatives.
10. The perovskite solar cell based on a moiré lattice structure according to claim 1, characterized in that: The back electrode is at least one of gold (Au), silver (Ag), copper (Cu), and aluminum (Al).
11. The method for preparing a perovskite solar cell based on a moiré lattice structure according to any one of claims 1 to 10, characterized in that: The steps include: A substrate is provided, on which a hole transport layer, a perovskite layer, a perovskite passivation layer, an electron transport layer, a hole blocking layer and a back electrode are sequentially prepared, wherein the hole transport layer and the perovskite layer are prepared by laminating a PDMS film with a grating pattern, and the PDMS film with a grating pattern is deflected by 0 to 180 degrees in the laminating direction of the hole transport layer and the perovskite layer.
12. The method for preparing a perovskite solar cell based on a moiré lattice structure according to claim 11, characterized in that: The preparation of the hole transport layer includes: spin coating the hole transport layer solution on the substrate, pressing a PDMS film with a grating pattern on the hole transport layer film and annealing, and peeling off the PDMS film to obtain a hole transport layer with a grating structure.
13. The method for preparing a perovskite solar cell based on a moiré lattice structure according to claim 11, characterized in that: The preparation of the perovskite layer includes: spin coating a perovskite precursor solution on the hole transport layer to form a perovskite wet film, pressing the PDMS film with a grating pattern on the wet film, and peeling off the PDMS film after annealing to obtain a perovskite layer with a grating structure.
Citation Information
Patent Citations
Condensation type perovskite solar module
CN116981271A
Perovskite solar cell and preparation method thereof
CN117545286A